1983
DOI: 10.1007/bf00236807
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between cat striate cortex neurons

Abstract: A series of simultaneous recordings from several striate cortex neurons were made in paralyzed, anesthetized cats. Recordings were obtained with one or two bundles of extra fine wires and originated from one and two cortical orientation columns. Standard PST histograms and, in some cases, response planes were used to analyse the neuronal receptive fields. Functional connectivity between neurons was assessed by cross-correlation of their spike trains. It was found that 61% of neuronal pairs found within a colum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
70
1

Year Published

1987
1987
2006
2006

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(81 citation statements)
references
References 28 publications
10
70
1
Order By: Relevance
“…If we examine orientation preference differences only for cell pairs with covariation strengths in class 4, as in Figure 6C, it is apparent that even among strong covariations there is no relationship between orientation preference and covariation strength. The lack of a relationship between correlations and orientation preference is markedly different from findings in cat (Michalski et al, 1983;Ts'o et al, 1986).…”
Section: Functional Horizontal Interactions Between V1 Cellscontrasting
confidence: 91%
See 2 more Smart Citations
“…If we examine orientation preference differences only for cell pairs with covariation strengths in class 4, as in Figure 6C, it is apparent that even among strong covariations there is no relationship between orientation preference and covariation strength. The lack of a relationship between correlations and orientation preference is markedly different from findings in cat (Michalski et al, 1983;Ts'o et al, 1986).…”
Section: Functional Horizontal Interactions Between V1 Cellscontrasting
confidence: 91%
“…6 B). Cells closer than 300 m were much more likely to show class 3 or class 4 covariation strength than cells separated by 300 -600 m and cells separated by more than 600 m. This distance dependency is very similar to results reported in cat V1 by Das and Gilbert (1999), who examined correlations in pairs of neurons at relatively short distances (most separations Ͻ600 m) but is different from Michalski et al (1983), who specifically targeted cells in adjacent orientation columns separated by up to 1 mm and reported that 40% of such cell pairs showed significant interactions. The lack of high correlations at longer distances in squirrel is in good agreement with the anatomical data that shows a rapid drop-off in the number of connections with distance and a lack of patchy regions at long distances that might have shown strong functional interactions.…”
Section: Functional Horizontal Interactions Between V1 Cellssupporting
confidence: 85%
See 1 more Smart Citation
“…To achieve strong orientation tuning typically observed in V1, recurrent excitatory and inhibitory connections are introduced among the model V1 cells. Following the experimental evidence (Ferster 1986;Michalski et al 1983), both excitatory and inhibitory connections in the model are strongest among cells with the same preferred orientation, and they drop off with increasing difference between the preferred orientations of the cells (Fig. 1B).…”
Section: Simulating Learning and Adaptation In A Recurrent Modelsupporting
confidence: 66%
“…On the other hand, the parameter given by the ratio of the number of correlated spikes relative to the number of the postsynaptic spikes has been proposed as the "contribution" by LEVICK et al [52]. Although this parameter cannot express the synaptic connectivity [1], this measured parameter has been used by many investigators to express the connectivity [63,[82][83][84]. KWAN et al [51] have proposed the combination of these two ratios to express synaptic strength.…”
Section: Quantitative Expression Of Cross-correlationmentioning
confidence: 99%